If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 123 + -6x = 21x + 18 Reorder the terms: 123 + -6x = 18 + 21x Solving 123 + -6x = 18 + 21x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21x' to each side of the equation. 123 + -6x + -21x = 18 + 21x + -21x Combine like terms: -6x + -21x = -27x 123 + -27x = 18 + 21x + -21x Combine like terms: 21x + -21x = 0 123 + -27x = 18 + 0 123 + -27x = 18 Add '-123' to each side of the equation. 123 + -123 + -27x = 18 + -123 Combine like terms: 123 + -123 = 0 0 + -27x = 18 + -123 -27x = 18 + -123 Combine like terms: 18 + -123 = -105 -27x = -105 Divide each side by '-27'. x = 3.888888889 Simplifying x = 3.888888889
| y^2-10y+12=0 | | 6r+11=89 | | -.11x-6=-1 | | 7t+53=14+6t | | x^2-4x+140=0 | | 2x-5=2x-6 | | 9-12x-x^2=0 | | (2x+5)(6x+4)= | | 3x-x=10x-66 | | 47=2x+7x-7 | | (7p+5q)(-2p+6q)= | | -2+4x=14 | | 0=z^2-6z+5 | | 6x+102=15x-6 | | -2x+6y=15 | | -2p=40 | | 18-3u=9 | | 66=7 | | 7+3x=8(3+x) | | -7x+2=-5 | | 5x^2-9x-89= | | 20+x=25 | | -7(e-6)+4(4e+5)= | | 6x+17=77 | | -6(x-8)=-6x+48 | | 17a-32=4+13a | | 2x-7x+6=0 | | 0=-2t^2+6t+3.5 | | 22=x^2-13x | | 5w=-6w+11 | | 0.36=.15x | | x+2x=8 |